Knowledge Shapes Decisions: The Evolving EU Experience with Tech Giant Mergers - Maggiolino, Mariateresa; Zoboli, Laura (Oxford University Press, 2025)
This paper analyzes the European Commission's evolving approach to mergers in digital markets, as reflected in its decision to block Booking's acquisition of eTraveli. The case exemplifies a shift toward assessing mergers within digital ecosystems, where long-term risks of dominance may outweigh short-term efficiencies. By situating this decision within two decades of cases involving tech giants, the paper shows how the Commission has progressively refined its understanding of digital market dynamics. It argues that Booking/eTraveli is not a rupture but a continuation of a broader, deliberate evolution in merger enforcement.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 8 - Trabajo decente y crecimiento económico